ACE and response to pulmonary rehabilitation in COPD: two observational studies. Issue 1 (8th March 2017) - Kon, Samantha S C; Jolley, Caroline J; Shrikrishna, Dinesh; Montgomery, Hugh E; Skipworth, James R A; Puthucheary, Zudin; Moxham, John; Polkey, Michael I; Man, William D-C; Hopkinson, Nicholas S
Abstract : Introduction: Skeletal muscle impairment is an important feature of chronic obstructive pulmonary disease (COPD). Renin–angiotensin system activity influences muscle phenotype, so we wished to investigate whether it affects the response to pulmonary rehabilitation. Methods: Two studies are described; in the first, the response of 168 COPD patients (mean forced expiratory volume in one second 51.9% predicted) to pulmonary rehabilitation was compared between different ACE insertion/deletion polymorphism genotypes. In a second, independent COPD cohort (n=373), baseline characteristics and response to pulmonary rehabilitation were compared between COPD patients who were or were not taking ACE inhibitors or angiotensin receptor antagonists (ARB). Results: In study 1, the incremental shuttle walk distance improved to a similar extent in all three genotypes; DD/ID/II (n=48/91/29) 69(67)m, 61 (76)m and 78 (78)m, respectively, (p>0.05). In study 2, fat free mass index was higher in those on ACE-I/ARB (n=130) than those who were not (n=243), 17.8 (16.0, 19.8) kg m −2 vs 16.5 (14.9, 18.4) kg/m 2 (p<0.001). However change in fat free mass, walking distance or quality of life in response to pulmonary rehabilitation did not differ between groups. Conclusions: While these data support a positive association of ACE-I/ARB treatment and body composition in COPD, neither treatment to reduce ACE activity nor ACE (I/D) genotype influence response to pulmonary rehabilitation.